Dermatology mycology diagnostics in Ireland: National deficits identified in 2022 that are relevant internationally. Issue 3 (9th December 2022) - Powell, James; Porter, Emma; Rafferty, Siobhan; Field, Sinead; O'Connell, Nuala H.; Dunne, Colum P.
Abstract: Background: Conventional testing methods for dermatophytes are time‐consuming, and resource limitations in our institution have prompted curtailed access to these diagnostics. Objectives: Evaluation of our hospital's dermatological mycology diagnostic services and similar services nationally. Methods: This was a retrospective observational study on skin, hair and nail mycology samples in our institution comparing twenty five‐year periods (2011–2015 and 2016–2021), including analysis of dermatology clinic data and correspondence related to fungal infection. A survey of national public hospitals' laboratories was conducted to evaluate their mycology testing capabilities. Results: The total 5 year test count prior to curtailment was 4851 specimens comprising 90% ( n  = 4344) from general practice and 6% ( n  = 290) from dermatology clinics. For the 5 years post curtailment, 64.5% (582/903) of specimens were from dermatology clinics. Dermatology clinic data demonstrated doubling of attendances (for all conditions) and of correspondence related to fungal infection. During this time also, national dermatological antifungal purchasing increased 11%. Ten of 28 Irish public hospital laboratories reported the provision of in‐house dermatological mycology testing, and none had routine availability of susceptibility or molecular testing of dermatophytes. Conclusion: This study is the first to report an appraisal of dermatological fungal diagnostic services in Ireland. Insufficient testing capacity implies that patients are either being treated for fungal infection without appropriate diagnostic confirmation, or being left untreated because of the lack of access to diagnostics. The introduction of molecular detection methods and susceptibility systems would enhance testing capabilities and reduce the requirement for the external referral.